United States : 2004 Article IV Consultation-Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that following a rather tepid recovery, the United States economy gathered strength in 2003. Supported by continued robust productivity growth, real GDP growth began to exceed the growth rate of potential output around midyear. The recovery broadened in early 2004 as payroll employment strengthened, easing concerns that a lack of employment growth and correspondingly weaker household income could weigh on consumer demand. Strong productivity growth has also contributed to significant improvements in corporate and financial balance sheets.